Problematic Smartphone Use and Communication in Families with Adolescents - Marina Merkaš; Matea Bodrožić Selak; Ana Žulec Ivanković (MDPI AG, 2024)
Research examining the relations among adolescent's problematic smartphone use, parent-adolescent conflicts about smartphone use, family communication, and adolescent communication skills is scarce. Thus, the study empirically examined a model of the direct and indirect effects of adolescents' problematic smartphone use on adolescent communication skills via family communication and parent-adolescent conflicts about smartphone use. The data used for the creation of this paper came from a sample of 284 adolescents (59.4% girls), aged 10 to 15, who participated in a four-wave longitudinal study (2021-2023) examining the effects of smartphone use on well-being and development. Adolescents rated their problematic smartphone use (wave 1), conflicts with parents about their smartphone use (wave 2), family communication (wave 3), and communication skills (wave 4). There was no support for the direct effect of problematic smartphone use on communication skills. Our path analysis showed a significant indirect effect of problematic smartphone use on communication skills via family communication. Our analysis also showed a significant direct effect of problematic smartphone use on conflicts between parents and adolescents about the time spent using smartphones and balancing activities with smartphone use. The findings of this study imply that excessive and extensive smartphone use may pose a risk factor for frequent parent-adolescent conflicts, poor family communication, and poor adolescent communication skills.